Исследование комплексов акриловых эфиров с тетрахлоридом титана - Бондалетов В. Г. Владимир Григорьевич; Бондалетов О. В. Олег Владимирович; Бондалетова Л. И. Людмила Ивановна; Бочкарев В. В. Валерий Владимирович (Химия, 2011)
Заглавие с титульного листа